Project raw gems : a campaign to promote the employment of people with autism in Singapore - Cheong, Yiling (2012)
This paper details the collaborative efforts between Project Raw Gems team and the Autism Resource Centre (Singapore). This campaign aims to raise awareness about autism in Singapore, and educate target publics about the employability potential of people with autism, if they are given proper training and support. To do this, the team organised a public communications campaign that targets three distinct publics – employers, family caregivers and the general public. The fulfilment of these objectives demands the pre-requisites of research, publicity, event planning and evaluation. Therefore, this campaign employs a variety of these measures, which form the components of a strategic public communications campaign. The report incorporates a survey of the current situation in Singapore, which is supplemented by formative research, followed by campaign strategies, execution and finally, results and reflection.